Inborn Errors of Immunity With Fetal or Perinatal Clinical Manifestations - Carneiro-Sampaio, Magda; Jesus, Adriana Almeida de; Bando, Silvia Yumi; Moreira-Filho, Carlos Alberto (Frontiers in Pediatrics, 2022)
In this article we revised the literature on Inborn Errors of Immunity (IEI) keeping our focus on those diseases presenting with intrauterine or perinatal clinical manifestations. We opted to describe our findings according to the IEI categories established by the International Union of Immunological Societies, predominantly addressing the immunological features of each condition or group of diseases. The main finding is that such precocious manifestations are largely concentrated in the group of primary immune regulatory disorders (PIRDs) and not in the group of classical immunodeficiencies. The IEI categories with higher number of immunological manifestations in utero or in perinatal period are: i) diseases of immune dysregulation (HLH, IPEX and other Tregopathies, autosomal recessive ALPS complete lack of FAS protein expression) and ii) autoinflammatory diseases (NOMID/CINCA, DIRA and some interferonopathies, such as Aicardi-Goutières syndrome, AGS, and USP18 deficiency). Regarding the other IEI categories, some patients with Omenn syndrome (an atypical form of SCID), and a few X-linked CGD patients present with clinical manifestations at birth associated to immune dysregulation. The most frequent clinical features were hydrops fetalis, intrauterine growth retardation leading to fetal loss, stillbirths, and prematurity, as in HLH and IPEX. Additionally, pseudo-TORCH syndrome was observed in AGS and in USP18 deficiency. The main goal of our review was to contribute to increasing the medical awareness of IEI with intrauterine and perinatal onset, which has obvious implications for diagnosis, treatment, and genetic counseling.